2022
DOI: 10.3390/cancers14071637
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, Oxidative Stress and Cancer Development

Abstract: Autophagy is an important cellular repair mechanism, aiming at sequestering misfolded and dysfunctional proteins and damaged cell organelles. Dysfunctions in the autophagy process have been linked to several diseases, like infectious and neurodegenerative diseases, type II diabetes mellitus and cancer. Living organisms are constantly subjected to some degree of oxidative stress, mainly induced by reactive oxygen and nitrogen species. It has been shown that autophagy is readily induced by reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 179 publications
(229 reference statements)
0
18
0
Order By: Relevance
“…therefore, autophagy discussed in this study refers specifically to macro-autophagy. Autophagy is involved in various physiological and pathological processes within an organism, including development, [75] tumor suppression, [76][77][78] antigen presentation, [79,80] cellular survival, [81] programmed cell death, [82,83] inflammatory balance, [84] and aging. [85,86] It primarily functions as a cellular protective mechanism that requires rigorous regulation.…”
Section: Mechanisms Underlying Autophagymentioning
confidence: 99%
“…therefore, autophagy discussed in this study refers specifically to macro-autophagy. Autophagy is involved in various physiological and pathological processes within an organism, including development, [75] tumor suppression, [76][77][78] antigen presentation, [79,80] cellular survival, [81] programmed cell death, [82,83] inflammatory balance, [84] and aging. [85,86] It primarily functions as a cellular protective mechanism that requires rigorous regulation.…”
Section: Mechanisms Underlying Autophagymentioning
confidence: 99%
“…4.1 Nutritional strategies: Fasting, phytochemicals, phytomelatonin, and fermented food 4.1.1 Fasting Fasting is an effective way to recover mitochondrial efficiency, and multiple human studies have shown its ability to restore metabolic pathways in people suffering from chronic pathologies. Fasting regimens are promising primary and secondary prevention strategies in patients suffering from metabolic and cardiovascular diseases (Oliveira et al, 2022;Papakonstantinou et al, 2022;Vasim et al, 2022;Zang et al, 2022), pain, inflammation and immune conditions (Feng et al, 2022;Fitzgerald et al, 2022;Parveen and Alhazmi, 2022), cancer (Lv et al, 2014;Marinac et al, 2016;Taucher et al, 2022;Tiwari et al, 2022), and neurological diseases characterized by altered mood, sleep, pain, and cognition (Phillips, 2019;Brocchi et al, 2022;Caron et al, 2022;Feng et al, 2022;Lobo et al, 2022;Xu et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…There is a system that inhibited free radical reaction in the body, so that excessive free radicals in the body are scavenged [45]. However, if this reaction system is damaged, excessive free radicals will directly cause damage to human cells [46]. It could be seen that the generation of oxidative stress in organisms is caused by the increase in the number of free radicals or the decline in the antioxidant defense function [47].…”
Section: Ligand Fishing Assay For Selaginella Doederleinii Ethyl Acet...mentioning
confidence: 99%